Contribution of ultra-processed foods in visceral fat deposition and other adiposity indicators: Prospective analysis nested in the PREDIMED-Plus trial. Issue 6 (June 2021) - Konieczna, Jadwiga; Morey, Marga; Abete, Itziar; Bes-Rastrollo, Maira; Ruiz-Canela, Miguel; Vioque, Jesus; Gonzalez-Palacios, Sandra; Daimiel, Lidia; Salas-Salvadó, Jordi; Fiol, Miguel; Martín, Vicente; Estruch, Ramón; et al.
Summary: Background & aims: Ultra-processed food and drink products (UPF) consumption has been associated with obesity and its-related comorbidities. Excess of visceral fat, which appears with increasing age, has been considered as the culprit contributing to adiposity-associated adverse health outcomes. However, none of previous studies elucidated the link between UPF and directly quantified adiposity and its distribution. We aimed to prospectively investigate the association between concurrent changes in UPF consumption and objectively assessed adiposity distribution. Methods: A subsample of 1485 PREDIMED-Plus participants (Spanish men and women aged 55–75 years with overweight/obesity and metabolic syndrome) underwent body composition measurements. Consumption of UPF at baseline, 6 and 12 months was evaluated using a validated 143-item semi-quantitative Food Frequency Questionnaire. Food items (g/day) were categorized according to their degree of processing using NOVA system. Regional adiposity (visceral fat (in g) and android-to-gynoid fat ratio) and total fat mass (in g) at three time points were measured with dual-energy X-ray absorptiometry (DXA) and were normalized using sex-specific z-scores. The association of changes in UPF consumption, expressed as the percentage of total daily intake (daily g of UPF/total daily g of food and beverage intake∗100), with adiposity changes was evaluated using linear mixed-effects models. Results: On average, the consumption of UPF accounted for 8.11% (SD 7.41%) of total daily intake (in grams) at baseline. In multivariable-adjusted model, 10% daily increment in consumption of UPF was associated with significantly (all p-values <0.05) greater accumulation of visceral fat (β 0.09 z-scores, 95% CI 0.05; 0.13), android-to-gynoid fat ratio (0.05, 0.00; 0.09) and total fat (0.09, 0.06; 0.13). Conclusion: A higher consumption of UPF was associated with greater age-related visceral and overall adiposity accumulation. Further studies are warranted to confirm these results in other populations and settings. Trial registration: The trial was registered at the International Standard Randomized Controlled Trial (ISRCTN: http://www.isrctn.com/ISRCTN89898870 ) with number 89898870 and registration date of 24 July 2014, retrospectively registered.